The role of fish as predators of krill (Euphausia superba) and other pelagic resources in the Southern Ocean - Kock, K. H.; Barrera Oro, Esteban; Belchier, M.; Collins, M. A.; Duhamel, G.; Hanchet, S.; Pshenichnov, L.; Welsford, D.; Williams, R.
Krill forms an important part of the diet of many Antarctic fish species. An understanding of the role of fish as krill predators in the Southern Ocean is critical to understanding how changes in fish abundance, such as through fishing or environmental change, are likely to impact on the food webs in the region. First attempts to estimate the krill and pelagic food consumption by Antarctic demersal fish in the low Antarctic were made in the late 1970s/ early 1980s. Those estimates were constrained by a paucity of biomass estimates and the mostly qualitative nature of food studies. Food consumption estimates were extended to the mesopelagic realm and the high-Antarctic Zone in the late 1980s and early 1990s when these areas were exploited commercially for Electrona carlsbergi. Currently, the best estimates of annual krill consumption by fish are 23 000 000–29 000 000 tonnes of krill and other pelagic prey taken annually by demersal fish in the 1980s in the whole Southern Ocean, and 5 000 000–32 000 000 tonnes taken by mesopelagic fish in the Atlantic sector of the Southern Ocean. It is clear from this review that fish are important predators of krill, in particular the larger myctophids and some channichthyids and nototheniids, and that the importance of krill in fish diets varies substantially both with time and location on various scales, as well as with the availability of alternate prey in the different regions in the Southern Ocean. Ecosystem models therefore need to account for their role. However, several key areas of uncertainty exist, which need to be considered in ecosystem and food-web models for the Southern Ocean. For instance, no robust estimates of food consumption by mesopelagic fish can be provided for the vast areas of the Indian and Pacific Ocean sectors, or for several of the most abundant myctophid species in the Atlantic sector, due to the paucity of relevant studies in these regions. Where biomass estimates do exist, such as in the Atlantic sector, there can be a lack of precision in trawl ...